Frequency of Severe Single Vessel Coronary Artery Disease in Patients with Unstable Angina - Idrees, Muhammad; Khan, Muhammad Nauman; Naseeb, Khalid; Jamil Ur Rahman; Shakil, Muhammad; Zada, Shakir (Indus Journal of Bioscience Research, 2025)
Background: Unstable angina (UA) is a high-risk manifestation of coronary artery disease (CAD) requiring early risk stratification and diagnostic evaluation. Objective: This study aimed to determine the frequency and clinical distribution of severe SVCAD in patients presenting with unstable angina. Methods: A cross-sectional study was conducted at the Department of Cardiology, NICVD Karachi, from 14th February 2025 to 14 May 2025. A total of 356 patients aged 40–80 years diagnosed with unstable angina were enrolled using non-probability sampling. Coronary angiography was performed to assess the presence and severity of single vessel disease. Results: Out of 356 patients, 131 (36.8%) were found to have severe SVCAD. The left anterior descending (LAD) artery was the most commonly involved vessel (65.6%), followed by the right coronary artery (22.1%) and left circumflex artery (12.2%). SVCAD was significantly more prevalent among males (p = 0.01), patients under 60 years of age (p = 0.03), and smokers (p = 0.02). No significant associations were observed with diabetes, hypertension, or residence status. Conclusion: Severe single vessel coronary artery disease is frequently observed in patients presenting with unstable angina, particularly among younger, male, and smoking populations. These findings emphasize the need for early angiographic evaluation and appropriate intervention, even in UA patients without multivessel disease features.